1999
DOI: 10.3354/cr012001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of downscaling models for changed climate conditions: case study of southwestern Australia

Abstract: Statistical downscaling of general circulation models (GCMs) and limited area models (LAMs) has been promoted as a method for simulating regional-to point-scale precipitation under changed climate conditions. However, several studies have shown that downscaled precipitation is either insensitive to changes in climatic forcing, or inconsistent with the broad-scale changes indicated by the host GCM(s). This has been recently attributed to the omission of the effect that changes in atmospheric moisture content ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(136 citation statements)
references
References 35 publications
3
131
0
2
Order By: Relevance
“…Even though one of the most important assumptions of any statistical downscaling technique is the stationarity of the parameters used (Wilby, 1997), there is no assurance that the relationship of the predictors and the predictants will not change in the future (Maheras et al, 2004). In this sense, the downscaled results should be interpreted cautiously (Charles et al, 1999).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Even though one of the most important assumptions of any statistical downscaling technique is the stationarity of the parameters used (Wilby, 1997), there is no assurance that the relationship of the predictors and the predictants will not change in the future (Maheras et al, 2004). In this sense, the downscaled results should be interpreted cautiously (Charles et al, 1999).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Karl et al, 1990;Wilby and Wigley, 1997;Murphy, 2000;Beckmann and Buishand, 2002); particularly as it may be an important predictor under a changed climate. Indeed, the inclusion of moisture variables as predictors can lead to convergence in the results of statistical and dynamical approaches (Charles et al, 1999), with the inclusion of GCM precipitation as a predictor also improving downscaling skill (Salathé, 2003;Widmann et al, 2003). Cavazos and Hewitson (2005) have performed the most comprehensive assessment of predictor variables to date, assessing 29 NCEP reanalysis variables using an artificial neural network (ANN) downscaling method in 15 locations.…”
Section: Statistical Downscalingmentioning
confidence: 99%
“…The introduction of the extra unobservable stochastic state is the primary difference between this and other multi-site methods, potentially allowing a more flexible structure for linking atmospheric variables to rainfall temporal and spatial patterns . The model has been applied widely in Australian catchments over a range of climates for different purposes, including water resources assessment and climate change analysis (Charles et al, 1999b(Charles et al, , 2004(Charles et al, , 2007Mehrotra et al, 2004;Robertson et al, 2006), and has been found capable of reproducing the magnitude and inter-annual variability of rainfall during dry and wet periods. As with most multi-site models, NHMMs may need a large number of parameters to satisfactorily reproduce observed rainfall, potentially creating high uncertainty in simulations.…”
Section: Multi-site Stochastic Rainfall Modelsmentioning
confidence: 99%